RIVER, RESISTANCE AND WOMEN’S RESILIENCE IN INDONESIAN, MALAYSIAN AND VIETNAMESE FICTIONS - Dewi, Novita (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2020)
This study looks at how rivers, resistance and women’s struggle intertwine with each other in 3 fictions set in, respectively, Indonesia, Malaysia and Vietnam. Not only has a river become life-giving forces, but it is also a locus of diverse social conflicts where women are often the most victimized yet survived. Making use of ecofeminism and related theoretical concepts such as Pope Francis’ encyclical Laudato si’ on the environment and human ecology, this study examines the female characters and their ordeals in the three fictions discussed. This study reveals that first, ecological economy depends on water sustainability where women try very hard to protect nature against degradation. Secondly, abuse of women is seen in parallel with abuse of nature. In the end, this study concludes that the women’ resistance against patriarchy confirms the theoretical relevance of ecofeminism for the reading of Southeast Asian fictions.